Nephritogenicity of glomerular basement membrane: a molecular aspect - Syarifuddin Rauf (Indonesian Pediatric Society Publishing House, 2001)
Glomerular basement membrane (GBM) has multifunctions. One of its functions is having nephritogenicitywhich means the ability of an antigen originally from GBM in causing glomerulonephritis, either in experimental animal or in human being. Recent studies on GBM have revealed that its main component is type IV collagen, consists of 6 different isoforms, α1 (IV) to α 6 (IV) chains. Genetic studies show that all of the six α chains are encoded by genes located in 2, 13, and X chromosomes. Nephritogenic antigen in GBM has been identified as α3, α4, α5 chains. They are molecules of type IV collagen located in globular domain (NC1 domain) at the carboxyl terminus of the type IV collagen of GBM. They are thought to assemble into a α3- α4- α5 (IV) chain helical molecules in human GBM. Other α chains, namely α1 and α2 chain, are not nephritogenic or poorly nephritogenic, while the α6 chain is not located in GBM. The nephritogenicity of GBM has been elucidated as a cause in experimental anti-GMB nephritis, and in Goodpasture and Alport syndromes.